(untitled) (Journal of Nepal Geological Society, 1982)
Palung massif which has a sharp contact with the country rocks, is one of those six granitic bodies that are situated in the Mahabharat Range of Central Nepal. This massif is a multiphase intrusive containing a number of facies rock varieties. The most widely distributed facies are coarse grained inequigranular porphyritic tourmaline granites in the central part and inequigranular tourmaline granites with portions of micropegmatitic texture in the apical part. Mineralogical and geochemical studies reveal that these granites are probably leucocratic differentiate of palingenetic granitic magma.